A BUSINESS PROCESS SIMULATION FRAMEWORK INCORPORATING THE EFFECTS OF ORGANIZATIONAL STRUCTURE - Lee, Jinyoun; Sung, Sanghyun; Song, Minseok; Choi, Injun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Organizations constantly change their business processes and/or organizational structure to innovate and adapt to the rapidly changing environment. Business process simulation is one of the most popular methodologies for more effectively predicting the effects of process and organizational redesign. Most existing approaches, however, consider only business processes and not organizational structures that can significantly affect business process performance. This study presents a framework for incorporating the effects of organizational structure into business process simulation. Further, it demonstrates how to use and analyze the proposed model. Finally, a case study of the Korean prosecutor’s office is presented to illustrate the importance and feasibility of the proposed approach, which will enable a more precise prediction of the changes caused by process and organizational redesign